A Secure Coprocessor for Database Applications - Ramamurthy, Ravi; Eguro, Ken; Arasu, Arvind; Kaushik, Raghav; Kossmann, Donald; Venkatesan, Ramarathnam (23rd International Conference on Field Programmable Logic and Applications (FPL), 2013)
The scalability and availability of cloud computing makes it an ideal platform for many database applications. However, it is challenging to secure sensitive client information in a practical and rigorous manner against both external attackers and curious cloud administrators. In this paper, we describe a novel secure FPGA-based query coprocessor and discuss how it can be tightly integrated with a commercial database system such as SQL Server. This combination, called Cipherbase, leverages efficient division of labor – using a conventional untrusted cloud server to handle mundane database operations while sensitive data is segregated and processed in trusted hardware to ensure confidentiality. We examine the architectural design issues that affect the achievable performance of the system and report initial results demonstrating the effectiveness for real-world cloud database applications.